The dynamics of phytobenthos and its main drivers on abrasion platforms with vermetids (Alicante, Southeastern Iberian Peninsula) - TERRADAS FERNÁNDEZ, MARC; BOTANA GÓMEZ, CARLOS; VALVERDE URREA, MIGUEL; ZUBCOFF, JOSÉ JACOBO; RAMOS ESPLA, ALFONSO (Mediterranean Marine Science, 2018)
Abrasion platforms with vermetids shape unique seascapes and biotic assemblages that characterize several of the warm Mediterranean coasts. The composition, structural and seasonal dynamics of the platforms’ phytobenthos were examined at two Southeast Iberian locations through non-destructive sampling. The patterns observed were linked with environmental variables and grazers’ coverage, and we assessed their possible influence. Structural descriptors α-diversity and β-diversity were applied, pointing that depth and season-related variables were the major influencing drivers. Higher α-diversity and β-diversity values during winter and spring coincided with the production optimum of the community. A greater average water depth influences the abundance of both midlittoral and infralittoral taxa. The strong resemblance between the phytobenthos of these vermetid platforms and that on similar platforms in the Eastern and Central Mediterranean Sea suggests that these are affected by the same structuring mechanisms.